Yukawa-like confinement potential of a scalar particle in a Gödel-type spacetime with any l - Mahdi Eshghi; Majid Hamzavi (European Physical Journal C: Particles and Fields, 2018)
Abstract In this paper, we investigate the behavior of a scalar particle within the Yukawa-like potential in a Gödel-type space-time for any l. The behavior of a spinless particle is analyzed in the presence of a topological defect with analytical solutions to the Klein–Gordon equation. By using the generalized series and Nikiforov-Uvarof (NU) methods, we deduce the energy eigenvalues and eigenfunctions. We have discussed on the obtained results.